The CD4 Count and Viral Load Differences in HIV Patients with and without Infectious Posterior Uveitis at a Tertiary Hospital in Indonesia - Hidayat, Shofa Annesa; Zuhria, Ismi; Arfijanto, Muhammad Vitanata; Prastyani, Reni (Current Internal Medicine Research and Practice Surabaya Journal, 2025)
Introduction: The human immunodeficiency virus (HIV) compromises the immune system, making the monitoring of cluster of differentiation (CD4) counts and viral loads critical for assessing disease progression and opportunistic infection risks. Eye-related manifestations, such as uveitis, are common among HIV patients. The purpose of this study was to investigate the differences in CD4 count and viral load between HIV patients with infectious posterior uveitis and those without at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Methods: A retrospective study with an analytical observational design was conducted using the medical records of 75 HIV patients. The examined variables included CD4 count and viral load as independent variables, alongside the incidence and absence of infectious posterior uveitis as dependent variables. The inclusion criteria were HIV patients with regular follow-ups, thereby excluding those with irregular follow-ups. The analysis used the Mann-Whitney test, with p<0.05 indicating a statistically significant difference. Results: All 75 samples met the inclusion criteria for analysis. The majority of the patients were male (64%) and within the age range of 31 to 40 years (44%). Patients with infectious posterior uveitis had significantly lower CD4 counts (p<0.05) compared to those without the disease. However, no significant differences in viral loads (p>0.05) were observed between patients with posterior uveitis and those without. Conclusion: CD4 counts differ significantly between patients with infectious posterior uveitis and those without, while viral loads show no considerable differences.   Highlights: 1. This study highlights the differences in cluster of differentiation (CD4) lymphocyte count and viral load between HIV patients with infectious posterior uveitis and those without. 2. The findings may provide new insights into the immunological mechanisms underlying infectious posterior uveitis in persons living with HIV. 3. This work contributes to determining the factors that affect the development of infectious posterior uveitis and explores the potential use of CD4 lymphocyte count and viral load as biomarkers for the diagnosis and management of the disease.